Clinical outcomes of bilateral implantation of new generation monofocal IOL enhanced for intermediate distance and conventional monofocal IOL in a Korean population - Choi, Wan-Kyu; Han, Hyo Ji; Son, Hyeck Soo; Khoramnia, Ramin; Auffarth, Gerd U.; Choi, Chul Young (BMC ophthalmology, 2023)
Background: To compare the clinical outcomes of bilateral implantation of enhanced intermediate function intraocular lenses (IOLs) and standard monofocal IOLs. Methods: In this prospective, randomized, comparative controlled study, we compared the visual outcomes of patients who underwent bilateral cataract surgery at the Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, with either enhanced monofocal IOLs (Tecnis Eyhance, ICB00, Johnson and Johnson Vision Care, Inc) (Group 1) or standard monofocal IOLs (Tecnis, ZCB00, Johnson and Johnson Vision Care, Inc) (Group 2). The assessment included monocular and binocular uncorrected distance visual acuity (UDVA), uncorrected intermediate (UIVA at 60 cm) and near (UNVA at 40 cm) visual acuity, uncorrected defocus curves, contrast sensitivity testing (CST), and reading speed test using Quality of vision was evaluated using the Visual Function Questionnaire (VFQ-25). Results: At 3-months postoperatively, monocular and binocular outcomes of UIVA and UNVA were statistically significantly better in Group 1 (P < 0.05). The binocular uncorrected defocus curve of Group 1 showed statistically significantly better outcomes at vergence ranges of -1.5 to -4.0 D (P < 0.05). Significantly higher reading speed test was also observed in Group 1 in all ranges tested (1.0 to 0.1 LogMAR) (P < 0.05). There were no statistically significant differences in CST between groups. Conclusions: Bilateral implantation of enhanced monofocal IOLs provided better vision at intermediate and near distances compared to standard monofocal IOLs, while maintaining good distance vision and contrast sensitivity.